Tax Avoidance Strategy as Accounting Behavior: An Analysis of the Effects of Sales Growth, Leverage, and Firm Size - Frenky Situmorang; Rima Auliyamartha Agustina; Umatun Makhumah; Lilian Nyamwanza (PT. Riset Press International, 2026)
This study aims to analyze the effects of Sales Growth and Leverage on Tax Avoidance, with Company Size as a mediating variable, among food and beverage manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach using secondary data from financial and annual reports of food and beverage companies listed on the IDX for the period 2019–2023. The sampling technique used was purposive sampling, with a total of 15 companies over 5 years, resulting in 75 samples. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test the relationship between variables. The overall results of the study show that the variables Sales Growth, Leverage, and Company Size do not significantly explain tax avoidance practices among food and beverage companies in Indonesia. This finding indicates that a company's decision to engage in tax avoidance is not solely determined by sales growth, debt levels, or the size of its assets, but is more influenced by factors such as complex tax strategies, company policies, tax regulations, and corporate governance. This research provides theoretical contributions to the development of accounting and taxation, particularly regarding corporate tax behavior. Furthermore, fundamental company factors such as sales growth, leverage, and size are not necessarily the primary determinants of tax avoidance practices, thereby opening the door to exploring other, more relevant variables. This research also provides practical contributions to regulators and tax authorities in formulating more comprehensive oversight policies that focus not solely on a company's financial characteristics, and to corporate management in making more cautious decisions regarding tax strategies to avoid the risk of sanctions.